2023
DOI: 10.3390/life13010224
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence Trends and Molecular Epidemiology of Viral Hepatitis in Croatia

Abstract: Viral hepatitis is a significant cause of morbidity and mortality worldwide. In Croatia, hepatitis B virus (HBV) and hepatitis C virus (HCV) are widely distributed, especially in some high-risk groups such as people who inject drugs (PWID), prisoners, and highly promiscuous groups. The seroprevalence of HBV ranges from 7.0% in the general population to 38.8% in PWID, depending on the region. The seroprevalence of HCV is highest among PWID (29–75.5%) as compared to 0.9% in the general population. Analyzing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(72 reference statements)
1
0
0
Order By: Relevance
“…Seropositivity was significantly higher in one-year-old children (94.5% in 2017) compared to children who received a vaccine against HBV at the age of 12 years (65% in the same year), which might indicate a natural decline in anti-HBs levels over time, as previously demonstrated [ 25 , 26 ]. Data from many studies showed a prevalence of anti-HB seropositivity that was similar to our results and was significantly higher in children, adolescents, and young adults [ 5 , 6 , 27 , 28 ]. The highest coverage of HB vaccination and the highest anti-HBs seropositivity was at the age of 1–4 years.…”
Section: Discussionsupporting
confidence: 91%
“…Seropositivity was significantly higher in one-year-old children (94.5% in 2017) compared to children who received a vaccine against HBV at the age of 12 years (65% in the same year), which might indicate a natural decline in anti-HBs levels over time, as previously demonstrated [ 25 , 26 ]. Data from many studies showed a prevalence of anti-HB seropositivity that was similar to our results and was significantly higher in children, adolescents, and young adults [ 5 , 6 , 27 , 28 ]. The highest coverage of HB vaccination and the highest anti-HBs seropositivity was at the age of 1–4 years.…”
Section: Discussionsupporting
confidence: 91%
“…Although it is generally expected that IgG antibodies to TBEV remain detectable for a longer period compared to the virus itself, our study presents a contrasting scenario. This can be attributed to two key factors: The rapid slaughter of animals, which likely restricted the full development of their antibody response, and the seasonal aspect of our sample collection, conducted during summer when TBEV is known to be more active (Blomqvist et al., 2021; Vilibic‐Cavlek et al., 2023). As a result, the virus is detectable primarily during the initial clinical phase, highlighting the importance of using both serological and molecular methods for accurate diagnosis and treatment (Balogh et al., 2010; Grešíková et al., 1975).…”
Section: Discussionmentioning
confidence: 99%